The Influence of Rotor Converters on the Behavior of Static Rotor Resistance Control of Induction Motor under Supply Voltages Asymmetry - Hilmi Fadhil Ameen (Zanco Journal of Pure and Applied Sciences, 2023)
This paper examines the impact of harmonics generated by the power semiconductor devices in the rotor circuit of a Softly Rotor Resistance Variation Induction Motor Drive System (SRRVIMDS) operating under voltage asymmetry. The study evaluates the components of rotor currents, electromagnetic torque, and stator winding currents based on a detailed mathematical circuit model configuration. The analysis also investigates the stator winding distortion currents produced by electromagnetic induction in the stator windings due to the harmonic components of the rotor current. The paper provides relationships for estimating all harmonic order frequencies of the stator currents, rotor currents, and torque as a function of the stator frequency and rotor speed. The results show that the investigated currents have sufficient accuracy, except at a slip of one-sixth, where notable differences occur.